2019
DOI: 10.3390/ijms21010271
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Like Cells Generated from Human Umbilical Cord Lining-Derived Mesenchymal Stem Cells as a New In Vitro Model for Neuronal Toxicity Screening: Using Magnetite Nanoparticles as an Example

Abstract: The wide employment of iron nanoparticles in environmental and occupational settings underlines their potential to enter the brain. Human cell-based systems are recommended as relevant models to reduce uncertainty and to improve prediction of human toxicity. This study aimed at demonstrating the in vitro differentiation of the human umbilical cord lining-derived-mesenchymal stem cells (hCL-MSCs) into neuron-like cells (hNLCs) and the benefit of using them as an ideal primary cell source of human origin for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…hNLCs (at day 3 and 8) were examined under an inverted microscopy. Physico-chemical Fe3O4NPs properties in mesenchymal stem cell neurogenic differentiation medium (Table 2) were performed as detailed in De Simone et al [30]. The parameters were evaluated up to 48 h since fresh neurogenic medium was changed every 48 h.…”
Section: Intracellular Fe 3 O 4 Nps Detected By Perls' Prussian Blue mentioning
confidence: 99%
See 3 more Smart Citations
“…hNLCs (at day 3 and 8) were examined under an inverted microscopy. Physico-chemical Fe3O4NPs properties in mesenchymal stem cell neurogenic differentiation medium (Table 2) were performed as detailed in De Simone et al [30]. The parameters were evaluated up to 48 h since fresh neurogenic medium was changed every 48 h.…”
Section: Intracellular Fe 3 O 4 Nps Detected By Perls' Prussian Blue mentioning
confidence: 99%
“…Data are expressed as the mean ± (S.D.) of three measurements (data adapted from De Simone et al [ 30 ]).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Stem cells can offer the opportunity to model the reproducibility of rare phenotypes in vitro [ 20 ]. For example, neuronal toxicity of Fe 3 O 4 NPs has been demonstrated by using the in vitro differentiation of the human umbilical cord lining-derived-mesenchymal stem cells (hCL-MSCs) into neuron-like cells (hNLCs) as an ideal primary cell source of human origin [ 21 ]. The study demonstrated that hCL-MSCs can be easily differentiated into neuronal-like cells and the hNCLs are susceptible to Fe3O4NPs, thus, human primary cultures of neurons could be a new in vitro model for NPs evaluation [ 21 ].…”
mentioning
confidence: 99%